β-conglycinin combined with fenofibrate or rosuvastatin have exerted distinct hypocholesterolemic effects in rats - Ferreira, Ederlan S. [UNESP]; Silva, Maraiza A. [UNESP]; Demonte, Aureluce [UNESP]; Neves, Valdir Augusto [UNESP] (Springer Nature, 2012)
Background: There is increasing interest in non-pharmacological control of cholesterol and triglyceride levels in the plasma and diet-drug association represent an important area of studies. The objective of this study was to observe the hypocholesterolemic effect of soybean β-conglycinin (7S protein) alone and combined with fenofibrate and rosuvastatin, two hypolipidemic drugs. Methods. The protein and drugs were administered orally once a day to rats and the effects were evaluated after 28 days. Wistar rats were divided into six groups (n = 9): hypercholesterolemic diet (HC), HC+7S protein (300 mg.kg-1 day-1) (HC-7S), HC+fenofibrate (30 mg.kg-1 day-1)(HC-FF), HC+rosuvastatin (10 mg.kg-1 day-1)(HC-RO), HC+7S+fenofibrate (HC-7S-FF) and HC+7S+rosuvastatin (HC-7S-RO). Results: Animals in HC-7S, HC-FF and HC-RO exhibited reductions of 22.9, 35.8 and 18.8% in total plasma cholesterol, respectively. In HC-7S-FF, animals did not show significant alteration of the level in HC+FF while the group HC-7S-RO showed a negative effect in comparison with groups taking only protein (HC-7S) or drug (HC-RO). The administration of the protein, fenofibrate and rosuvastatin alone caused increases in the plasma HDL-C of the animals, while the protein-drug combinations led to an increase compared to HC-FF and HC-RO. The plasma concentration of triacylgycerides was significantly reduced in the groups without association, while HC-7S-FF showed no alteration and HC-7S-RO a little reduction. Conclusion: The results of our study indicate that conglycinin has effects comparable to fenofibrate and rosuvastatin on the control of plasma cholesterol, HDL-C and triacylglycerides, when given to hypercholesterolemic rats, and suggests that the association of this protein with rosuvastatin alters the action of drug in the homeostasis of cholesterol. © 2012 Ferreira et al; licensee BioMed Central Ltd.
Keywords: β-conglycinin; cholesterol-lowering drugs; hypercholesterolemic diet; rats.; beta conglycinin; fenofibrate; high density lipoprotein cholesterol; rosuvastatin; soybean protein; triacylglycerol; unclassified drug; beta conglycinin protein, Glycine max; beta-conglycinin protein, Glycine max; cholesterol; fluorobenzene; globulin; hypocholesterolemic agent; plant antigen; pyrimidine derivative; seed storage protein; sulfonamide; animal experiment; animal model; cholesterol blood level; controlled study; diet; hypercholesterolemia; hypocholesterolemia; male; nonhuman; rat; triacylglycerol blood level; animal; blood; drug combination; drug effect; drug potentiation; heart; heart muscle; isolation and purification; lipid diet; liver; metabolism; organ size; pathology; protein intake; soybean; Wistar rat; Animalia; Glycine max; Rattus; Rattus norvegicus; Animals; Anticholesteremic Agents; Antigens, Plant; Cholesterol; Diet, High-Fat; Dietary Proteins; Drug Combinations; Drug Synergism; Fenofibrate; Fluorobenzenes; Globulins; Heart; Hypercholesterolemia; Liver; Male; Myocardium; Organ Size; Pyrimidines; Rats; Rats, Wistar; Seed Storage Proteins; Soybean Proteins; Soybeans; Sulfonamides; Triglycerides